IMPLEMENTASI NILAI-NILAI PANCASILA DALAM DINAMIKA POLITIK - Fadhil, Muhammad; Ilham Hudi; Asrini; Putri Rama Sari; Ajeng Sofiantini; Angguni Desilva Sari; Dwinda Kayla Amartha; Rahma Dini Putri (Yayasan Panca Bakti Wiyata Pangandaran, 2024)
Pancasila, which represents the spirit and historical values of the nation, has never failed to be implemented in every activity of Indonesian society, including in the world of politics. This research aims to explore the implementation of Pancasila values in the dynamics of politics in Indonesia. The approach taken in this research uses a qualitative approach. Data for this research was collected using the literature study method, namely reading articles and journals related to the research problem. In fact, the values of Pancasila have not yet been fully implemented in the world of Indonesian politics. There are so many political activities carried out in Indonesia that are not in accordance with the noble values contained in Pancasila. Apart from that, violations of the principles of Pancasila seem to be something that is commonplace now so that the values of Pancasila are just a display. Keywords: Pancasila values, political dynamics, influence Abstrak Pancasila yang mewakili semangat dan nilai-nilai historis bangsa tidak pernah luput pengimplementasiannya dari setiap kegiatan masyarakat Indonesia, termasuk dalam dunia perpolitikan. Penelitian ini bertujuan untuk mendalami pengimplementasian nilai-nilai pancasila dalam dinamika berpolitik di Indonesia. Pendekatan yang dilakukan dalam penetilian ini menggunakan pendekatan kualitatif. Data untuk penelitian ini dikumpulkan dengan metode studi literatur yaitu seperti membaca artikel dan jurnal yang berkaitan dengan masalah penelitian. Nyatanya nilai-nilai pancasila sampai sekarang belum dapat diimplementasikan secara keseluruhan dalam dunia politik Indonesia. Begitu banyak kegiatan politik yang dilakukan di Indonesia yang tidak sesuai dengan nilai-nilai luhur yang terkandung dalam pancasila. Selain itu pelanggaran sila-sila dalam pancasila seakan-akan merupakan hal yang sudah lumrah terjadi sekarang sehingga nilai-nilai pancasila tersebut hanyalah menjadi pajangan semata.